2015
DOI: 10.1182/blood-2015-09-672592
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein enhances murine antibody–mediated transfusion-related acute lung injury

Abstract: Key Points• CRP enhances antibodymediated lung damage when infused into TRALI-resistant mice.• CRP and TRALI-inducing antibodies generate a synergistic increase in MIP-2 production and pulmonary neutrophil accumulation in vivo.Transfusion-related acute lung injury (TRALI) is a syndrome of respiratory distress triggered by blood transfusions and is the leading cause of transfusion-related mortality. TRALI has primarily been attributed to passive infusion of HLA and/or human neutrophil antigen antibodies present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 36 publications
2
54
2
Order By: Relevance
“…The first hit consists of a pre-disposing factor present in the recipient such as inflammation while the second hit is conveyed by factors present in the transfused blood product such as anti-leukocyte antibodies (3). For example, the acute phase protein C-reactive protein (CRP) which rapidly increases during infection and inflammation was shown to enhance antibody-mediated TRALI in mice (4) and in line with that data, CRP was found to be elevated in human TRALI patients (5) confirming its role as a first hit risk factor in human TRALI.…”
mentioning
confidence: 65%
“…The first hit consists of a pre-disposing factor present in the recipient such as inflammation while the second hit is conveyed by factors present in the transfused blood product such as anti-leukocyte antibodies (3). For example, the acute phase protein C-reactive protein (CRP) which rapidly increases during infection and inflammation was shown to enhance antibody-mediated TRALI in mice (4) and in line with that data, CRP was found to be elevated in human TRALI patients (5) confirming its role as a first hit risk factor in human TRALI.…”
mentioning
confidence: 65%
“…6,[10][11][12][13] Briefly, the right lung of each mouse was removed and weighed to determine the wet weight and then dried in an oven at 60°C for 48 hours. The dried samples were reweighed to obtain the dry weight.…”
Section: Lung W/d Weight Ratiosmentioning
confidence: 99%
“…2 Using animal models of antibodymediated TRALI, it has become clear that neutrophils (polymorphonuclear cells [PMNs]) are the major effector cells in TRALI. 6,[9][10][11][12][13] Moreover, using a novel C57BL/6 knockout (KO) model of antibodymediated TRALI, we recently demonstrated that PMN-reactive oxygen species are critically essential for inducing the acute lung injury in TRALI. 12 In addition, CD4 1 T regulatory cells and dendritic cells were identified as important suppressor cells of antibody-mediated TRALI and this protective response was associated with production of the anti-inflammatory cytokine IL-10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provides a novel and direct link between inflammation and TRALI, opening doors for possible new approaches in targeting TRALI. 1 T RALI is a syndrome characterized by acute respiratory distress resulting in acute lung injury within 6 hours upon blood transfusion. In the majority of the cases, antibodies against HLAs and/or human neutrophil antigen (HNA) present in the transfused product are thought to be responsible for initiating TRALI.…”
mentioning
confidence: 99%